The Demons of William James Religious Pragmatism Explores Unusual Mental States - Ruetenik, Tadd (Springer International Publishing, 2018)
This book is a psychological exploration of unusual minds, a religious exploration of demonological myth, and a philosophical exploration of the reaches of pragmatism. It uses topics such as hypnotism, mediumship, and mass possession to argue for a comprehensive understanding of the demonic that acknowledges not only the creativity which it encourages, but also the danger it can bring. Professor Ruetenik uses James' religious pragmatism to evaluate the relevance of psychical research, and to explain common beliefs regarding demons, spirits, and other controlling personalities. The conclusion of this interdisciplinary research is as alarming as it is fascinating: When exploring the demons of William James, we discover that ordinary personality cannot be clearly separated from what we consider the demonic.